230k views
2 votes
Solving Multi-step
5x-6=3(x-2)​

User Morgi
by
4.0k points

2 Answers

3 votes

Hello there! :)

Answer:


\boxed{x=0}

Explanation:

distributive property: a(b+c)=ab+ac

Expand form.

3(x-2)

3*x=3

3*2=6

3x-6

5x-6=3x-6

you add by 6 both sides of an equation.

5x-6+6=3x-6+6

add numbers from left/right

5x=3x

subtract 3x both sides of an equation.

5x-3x=3x-3x

simplify.

2x=0

then, you divide by 2 both sides of an equation.

2x/2=0/2

divide numbers from left/right.

0/2=0


\boxed{x=0}, which is our final answer.

Hope this helps!

Thanks!

-Charlie

Have a nice day! :)

User MatthewFord
by
4.7k points
7 votes

Answer:


x=0

Explanation:


5x-6=3\left(x-2\right)

Apply distributive property.


5x-6=3x-6


5x-6+6=3x-6+6


5x=3x


5x-3x=3x-3x


2x=0


(2x)/(2)=(0)/(2)


x=0

User Vadim  Kharitonov
by
4.9k points